The development of a novel, multilingual IBD knowledge questionnaire for Asian patients with inflammatory bowel disease - Nik Razima Wan Ibrahim; Mahmoud Danaee; Xin-Hui Khoo; Suresh Sithambaram; Shahreedhan Shahrani; Alex Hwong-Ruey Leow; Jo-Ven Chang; John Francis Mayberry; Ida Normiha Hilmi (BMC Gastroenterology, 2023)
Abstract Background Inflammatory bowel disease is an uncommon disease in developing nations whereby patient’s knowledge on the disease may be limited. The CCKNOW questionnaire, a widely known questionnaire to assess patient’s knowledge on the disease, may be too complex to comprehend for patients in developing countries. The aim of this study is to develop a new tool known as AIBDKQ questionnaire to evaluate the local inflammatory bowel disease patient’s knowledge. Methods This was a prospective study carried out in four phases. In phase 1, three gastroenterologists with expertise in IBD generated a total of 21 questions related to the general knowledge of the disease in the English language. Phase 2 involved content and face validity whereby the questions were further validated by other gastroenterologists. In phase 3, the validated questions were translated into three languages namely Malay, Mandarin and Tamil which are commonly used in Malaysia. In phase 4 (statistical validity), administration of the questionnaires to patients and hospital staff were conducted to assess the construct validity, discriminative ability, predictive validity and reliability of the questionnaires. Results A total of 21 questions were generated initially. Further evaluation indicated that 20 items had adequate kappa and content validity index for relevance (CVI: 0.714 to 1, Kapp: 0.645 to 1) and clarity (CVI: 0.714 to 1, Kapp: 0.645 to 1). The questionnaires in four languages were administered to 213 patients to assess the construct validity. Six items were removed (three for low communality, one for small loading factors, two for cross loading), resulting in 16 final questions. Assessment with 34 hospital staff involving nurses, doctors and clerks showed significant differences in knowledge between the groups (F = 14.007, p < 0.001) and were able to discriminate doctors from nurses and clerks. Another group of 18 hospital staff administered with AIBDKQ and CCKNOW questionnaires showed a Pearson’s correlation coefficient of 0.8 indicating strong correlation and concurrent predictive validity between the two questionnaires. Final assessment with 38 patients for reliability assessment revealed high intraclass correlation of the questionnaire among the four languages. Conclusions The AIBDKQ has an excellent discriminant ability and internal consistency with a strong correlation when compared to the standard CCKNOW questionnaire.